Experimental and mechanistic study on the enhanced CO2 capture using adjustable choline chloride-based DES - Wang, Jiaqiang; Liu, Dexin (European Journal of Sustainable Development, 2025)
Excessive emissions of carbon dioxide (CO2) in the environment have become a major factor contributing to global warming. The development of efficient, green, and sustainable absorbents for CO2 capture is urgently needed. In this study, a series of deep eutectic solvents (DES) were prepared by using choline chloride (ChCl) as the hydrogen bond acceptor (HBA) and ethylene glycol (Eg), glycolic acid (Gla), and monoethanolamine (MEA) as hydrogen bond donors (HBDs), each containing different HBDs. The results showed that the CO2 capture performance of the DESs containing different HBDs exhibited significant variations. Among them, the amino-type HBD (MEA) demonstrated the best absorption capacity at room temperature (1.65 mol CO2/kg DES), while non-amino-type HBDs (Eg, Gla) consistently followed the trend: Gla > Eg. In addition, this work combined FTIR, NMR, DFT calculations, and molecular dynamics simulations to reveal, from a microscopic perspective, the intrinsic mechanisms behind the differential CO2 capture abilities of the adjustable HBDs. Overall, this work reveals the significant contribution of the tunable HBDs to CO2 capture in DESs from a microscopic mechanistic perspective, providing a direction for the future development of green DESs with high absorption capacity. Keywords: CO2 capture, DES, HBD, DFT calculations, Molecular dynamics